Prosedur Pemberhentian Sementara Notaris dalam Perspektif Due Process of Law - Albert Dento (Jurnal Hukum Lex Generalis, 2025)
This study examines the procedure of temporary dismissal of notaries within the perspective of due process of law through a case study of Court Decision No. 20/Pdt.G/2017/PN Jkt.Sel. The research focuses on the relationship between the authority of the tiered Supervisory Council and the decision of the Minister of Law and Human Rights, as well as its relevance to Lon L. Fuller’s eight principles of the internal morality of law. The issue arises from inconsistencies between the Supervisory Council’s ruling and the absence of a Ministerial Decree, rendering the sanction legally baseless. The method applied is normative juridical descriptive with statutory, conceptual, and case approaches, analyzed deductively through qualitative reasoning. The findings reveal that administrative failure undermines sanction legitimacy and creates legal uncertainty, leading to recommendations for stronger supervisory mechanisms, digitalized reporting, and time limits for sanction proposals to ensure legal certainty and professional accountability of notaries.